Populist styles and meanings in Acun Medya reality shows - Gökçe Baydar Çavdar (Connectist Istanbul University Journal of Communication Sciences)
This article reflects on the relationship between popular culture and populism through Acun Medya reality shows that are influential in the popular culture realm. Inspired by populism scholars and television studies framework, the article considers populism as ‘style’ (us vs them, mobilizing emotions/emotionality, personality cult) and political meanings informed by conservative ideologies. This paper will first review the populist hegemony of right-wing ideologies and interventions on television content. Then it will situate the reality television and factual entertainment in the Turkish television landscape. Through multimodal discourse analysis of three factual entertainment shows of the latest seasons, MasterChef (2023), O Ses Turkiye- New Years Special (2023) and Survivor (2024), the article discusses populism both enabled and generated by the formats, the production company and ordinary people participating. In the findings section, the populist style in the shows is explored through us versus them dichotomy, emotional style and personality cults. Then, assumptions and constructions of family, audiences, fans, and nation are discussed. In the discussion and conclusion section, the article briefly highlights the differences between these programs and other reality shows and argues that in all programs, the ideals of nation and family are revisited and reaffirmed in various ways.